2021
DOI: 10.3390/jcm10102199
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Neutrophil-to-Lymphocyte Ratio Combined with Platelet-to-Lymphocyte Ratio as a Predictor of Survival Outcomes after Definitive Concurrent Chemoradiotherapy for Cervical Cancer

Abstract: The aim of the study was to evaluate pretreatment neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as prognostic factors for predicting clinical outcomes after definitive concurrent chemoradiotherapy (CCRT) for cervical cancer. The cases were divided into two groups based on the values of NLR and PLR: High NLR-PLR (high value in both NLR and PLR) and Low NLR-PLR (low value in either NLR or PLR). The relationships between survival outcomes and the pretreatment NLR-PLR were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…Lima et al reported an adverse association between NLR and prognosis in cervical cancer [ 36 ], whereas Zhang et al showed the correlation of preoperative NLR with unfavorable histopathological features and prognosis in patients with cervical cancer who underwent surgery [ 24 ]. Additionally, pretreatment NLR could be a prognostic factor after chemotherapy and radiotherapy for cervical cancer [ 19 , 22 , 37 ]. More recently, the adverse association between NLR and prognosis in patients treated with immunotherapy has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Lima et al reported an adverse association between NLR and prognosis in cervical cancer [ 36 ], whereas Zhang et al showed the correlation of preoperative NLR with unfavorable histopathological features and prognosis in patients with cervical cancer who underwent surgery [ 24 ]. Additionally, pretreatment NLR could be a prognostic factor after chemotherapy and radiotherapy for cervical cancer [ 19 , 22 , 37 ]. More recently, the adverse association between NLR and prognosis in patients treated with immunotherapy has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…21 In some studies PLR correlated with survival outcomes 19,22 while some found NLR to have correlation with survival outcomes, 15,20,23 whereas some found both NLR and PLR to correlate with poorer survival outcomes. 16,24,25 In this study, ROC curve analysis of local recurrence yielded the NLR cutoff value as 2.45 (AUC ¼ 0.839) with a sensitivity of 82.6% and specificity of 77.7% and the PLR cutoff value 140.6 (AUC ¼ 0.892) with a sensitivity of 85.5% and specificity of 80.6%. This matched with another study, the sensitivity value for NLR was 82% and specificity 71% with a cutoff of 3.38 using ROC analyses and 72 and 70% with cutoff of 172.05 for PLR, respectively, for predicting stage with NLR and PLR.…”
Section: Discussionmentioning
confidence: 67%
“…21 In some studies PLR correlated with survival outcomes 19 22 while some found NLR to have correlation with survival outcomes, 15 20 23 whereas some found both NLR and PLR to correlate with poorer survival outcomes. 16 24 25…”
Section: Discussionmentioning
confidence: 99%
“…This constitutes the scientific foundation, which allows the practitioner to evaluate, indirectly, the dimensions of inflammation in cancer, and these parameters NLR, PLR, and LMR are potential clinical prognostic markers. NLR has been repeatedly reported as a prognostic factor in ovarian cancer patients in advanced stages of the disease, 11,[66][67][68][69] in patients with other tumor locations 70,71 or may be useful in selecting patients for different types of immunotherapy. 66,72 Mechanisms of antineoplastic defense by activating innate immune cells.…”
Section: The Relationship Between the Chronic Inflammatory Process An...mentioning
confidence: 99%